1993
DOI: 10.1523/jneurosci.13-05-02068.1993
|View full text |Cite
|
Sign up to set email alerts
|

Sodium channels, GABAA receptors, and glutamate receptors develop sequentially on embryonic rat spinal cord cells

Abstract: It is not well understood when during embryonic development the elements of a cell's responsiveness first appear, nor the factors controlling their appearance. A strategy to approach this issue is to determine which aspects of neuronal development are highly stereotyped in presence, timing, or pattern across a variety of cell types, and which are more diversified by cell type, region, or other parameters. We have used a fluorescent potentiometric oxonol dye in conjunction with a digital video imaging system to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 60 publications
(72 reference statements)
7
65
0
Order By: Relevance
“…This is consistent with experiments near the beginning of hypothalamic neurogenesis (E1.5) when all cells tested with patch-clamp recording showed a large response to GABA, but only some showed a response to glutamate (van den Pal et al, 1995). Studies in the spinal cord showed that GABA receptors are expressed in early embryogenesis and may be found even earlier than glutamate receptors (Walton et al, 1993). GABA and its synthetic enzyme are found in E6 neurons in the chick retina (De Mello et al, 1976;Frederick, 1987); this is prior to significant synaptogenesis described at El4 (Sheffield and Fischman, 1970).…”
Section: Developmentalsupporting
confidence: 89%
“…This is consistent with experiments near the beginning of hypothalamic neurogenesis (E1.5) when all cells tested with patch-clamp recording showed a large response to GABA, but only some showed a response to glutamate (van den Pal et al, 1995). Studies in the spinal cord showed that GABA receptors are expressed in early embryogenesis and may be found even earlier than glutamate receptors (Walton et al, 1993). GABA and its synthetic enzyme are found in E6 neurons in the chick retina (De Mello et al, 1976;Frederick, 1987); this is prior to significant synaptogenesis described at El4 (Sheffield and Fischman, 1970).…”
Section: Developmentalsupporting
confidence: 89%
“…Neurons express functional GABA receptors very early in development (Fiszman et al, 1990;Walton et al, 1993;Chen et al, 1995). Some embryonic, but not mature, neurons show Ca 2ϩ rises in response to GABA (Reichling et al, 1994;Ben-Ari et al, 1989;Yuste and Katz, 1991;Obrietan and van den Pol, 1995a).…”
Section: Discussionmentioning
confidence: 99%
“…Integrated FL from pixels within each AOI were summed and FL of equivalent background areas subtracted before conversion to log(FL). The data acquisition process and software were developed in house by Walton et al (Walton et al, 1993) and further refined by the authors for the present application.…”
Section: Voltage Probe Recording and Data Analysismentioning
confidence: 99%